Representing and evaluating the travel motivations of Pacific islanders - Trupp, Alexander *; Pratt, Stephen; Stephenson, M. L. *; Matatolu, Ilisapeci; Gibson, Dawn (Wiley, 2022)
The mobility patterns and travel motivations of Pacific Islanders have largely been neglected by discourses and discussions on Asia-Pacific tourism. To examine the travel preferences and travel motivations of Pacific Islanders, we administered surveys (n = 1100) across the five Pacific Island States and Territories of Cook Islands, Fiji, Kiribati, Samoa and Solomon Islands. The research offers a comparative analysis across national boundaries by highlighting commonalities and differences among the five groups. Family, kinship and religious dimensions stand out as shared and crucial factors influencing travel preferences and travel motivations across the region. Nonetheless, the research identified differences between the Pacific communities which can be explained with each country's level of socioeconomic development, political structure, geography, cultural context and globalisation. The study advances knowledge on the mobilities and travel motivations of non-Western tourists by conceptualising the Pacific Islands from the perspective of a tourism-generating region.